Isolation of two strains of West Nile virus during an outbreak in southern Russia, 1999. - Lvov, D K (Centers for Disease Control and Prevention, 2000)
From July to September 1999, a widespread outbreak of meningoencephalitis associated with West Nile virus (Flavivirus, Flaviviridae) occurred in southern Russia, with hundreds of cases and dozens of deaths. Two strains of West Nile virus isolated from patient serum and brain-tissue samples reacted in hemagglutination-inhibition and neutralization tests with patients' convalescent-phase sera and immune ascites fluid from other strains of West Nile virus.